SEL151 : Sports reporting / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
The subject exposes students the basic of writing and reporting of news and subsequently reporting of news on sports as well as basics of advertising.